2020
DOI: 10.1186/s12879-020-05506-5
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent acute myositis and Guillain-Barre syndrome in Cytomegalovirus infection – a rare case report

Abstract: Background Cytomegalovirus (CMV) is a double stranded DNA virus and ubiquitous in nature. Association of Guillain-Barre syndrome (GBS) and CMV is well known but CMV acute myositis is a rare condition. Restriction of movements of limbs due to severe pain in myositis may obscure the diagnosis of GBS and this may easily miss. Case presentation Here we describe a 29-year-old male presenting with pain and swelling of bilateral lower limbs which progressed rapidly with increasing serum creatine kinase levels with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…GBS is a heterogeneous disorder characterized by rapidly progressive, symmetrical ascending paralysis with areflexia or hyporeflexia triggered by certain infections, such as C. jejuni, cytomegalovirus, M. pneumoniae, Epstein-Barr virus, and Zika virus [4][5][6][7]. Studies done in the past during the 1976 swine flu outbreak revealed that GBS developed after vaccination, with 8.8 cases per million recipients of influenza vaccine being documented [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS is a heterogeneous disorder characterized by rapidly progressive, symmetrical ascending paralysis with areflexia or hyporeflexia triggered by certain infections, such as C. jejuni, cytomegalovirus, M. pneumoniae, Epstein-Barr virus, and Zika virus [4][5][6][7]. Studies done in the past during the 1976 swine flu outbreak revealed that GBS developed after vaccination, with 8.8 cases per million recipients of influenza vaccine being documented [16].…”
Section: Discussionmentioning
confidence: 99%
“…GBS is usually preceded by an infectious trigger by bacterial or viral agents most commonly associated with infection caused by Campylobacter jejuni (C. jejuni) [4]. In addition, recent infections by the Zika virus, Epstein-Barr virus (EBV), and Cytomegalovirus (CMV) have also been reported as antecedent causes of GBS [5][6][7]. Severe acute respiratory syndrome (SARS-CoV-2) infection, resulting in the coronavirus disease 2019 (COVID-19) pandemic, is associated with Guillain-Barré syndrome (GBS) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Review of the medical literature identified 5 patient case reports of GBS that were complicated with RML ( Table 2 ) ( 5 9 ). Therefore, a total of 7 GBS patients experienced concomitant RML.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients initially experience muscle pain or nerve root pain ( 2 ). During the course of GBS, 16–27% of patients show an elevation of serum creatine kinase (CK) levels ( 3 , 4 ) but only rarely is GBS complicated with rhabdomyolysis (RML) ( 5 9 ). The research history of GBS in Beijing Children's Hospital (BCH), which is affiliated with Capital Medical University, can be traced back to the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous occurrence of GBS and acute myositis has been rarely reported in the literature in the context of acute viral myositis caused by Mycoplasma pneumoniae, Cytomegalovirus, and dengue virus. 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%